PENDIDIKAN AGAMA ISLAM SEBAGAI KATALISATOR ISLAMIC PARENTING: STUDI EMPIRIS PADA KELUARGA MUALLAF - Alfusanah, Fadilatul; Subandi; Fakhri, Jamal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the role of Islamic Religious Education as a catalyst in Islamic Parenting through an empirical study of convert families in Belitang III District, East OKU Regency. Using a qualitative approach, this study aims to describe the perceptions of convert parents, the implementation of Islamic Religious Education, and various problems encountered in its implementation. Data were collected through in-depth interviews with informants who are convert parents in the area, analyzed descriptively qualitatively to gain a holistic understanding. The results show that the majority of convert parents have a positive perception of Islamic Religious Education, considering it essential in shaping the character and morals of their children from an early age. The implementation of Islamic Religious Education in families is carried out actively through methods of role modeling, habituation, and motivation, with efforts to introduce prayer, daily prayers, and noble morals. Some families even send their children to Islamic boarding schools for better quality religious education. However, the main challenge includes the limited ability of convert parents to read the Quran or understand Arabic, forcing them to seek help from Quran teachers. Furthermore, institutional support after conversion is still perceived as less than optimal. Despite this, the social environment is generally supportive, encouraging convert families to remain steadfast in their Islamic faith. This study provides an overview of the dynamics of Islamic Religious Education within convert families, highlighting the need for more structured and sustainable religious guidance programs.